PERAN PENURUNAN BERAT BADAN TERHADAP KADAR PLASMINOGEN ACTIVATOR-1 PADA OBESITAS ABDOMINAL - Budhiarta, A.A.Gd. (journal of internal medicine, 2006)
Analytical cross-sectional study involving 77 subjects (male 31, female 46) with abdominal obesity (Ab-Ob) and 27 subjects non obese (male 20; female 7), age between 30-60 years were conducted and continued withrandomized pre-post test control group study involving 66 subjects (male 25, female 41) with Ab-Ob recruitedfrom the analytical cross-sectional study. Using random permuted block 30 subjects ( male 12; female 18) weretreated with hypocaloric diet and regular physical exercise for 12 weeks and 36 subjects (male 13; female 23) ascontrols. Compare with non obese subjects there were higher levels of active PAI-1, insulin and HOMA-IR insubjects with Ab-Ob (p<0.001 ; p = 0.001 and p < 0.001 respectively). There were significant correlation betweenfasting insulin level and HOMA-IR with active PAI-1 ( r = 0.488, p <0.001 and r = 0. 543, p <0.001 respectively).Among treated group decreased in body weight 5.9 kg or 7.4% followed by decreased in WC ( p <0.001), insulin(p = 0.005), and active PAI-1 (p <0.001). Among treated group decreased in WC ( p<0.001), insulin (p = 0.001),and active PAI-1 ( p = 0.003) were higher than control group. There were positive correlation between decreasedbody weight ( r = 0.297; p <0,001), decreased decreased FBS ( r = 0.307 ; p = 0.012), decreased insulin (r =0.360 ; p = 0.003), with decreased active PAI-1. To test the independence of associations between decreased inactive PAI-1 and decreased body weight, fasting blood sugar and insulin levels during program, a multivariatelinear regression analysis was performed. Only decreased in body weight and decreased fasting blood sugarsignificantly and independently associated with decreased in active PAI-1 and accounted for 23.4% of the varianceof decreased in active PAI-1. Decreased body weight accounted for 17.1% and decreased fasting blood sugaraccounted for 6.3% of decreased in active PAI-1.